Human factors and ergonomics in sport applications and future directions - Salmon, Paul M.; McLean, Scott; Dallat, Clare; Mansfield, Neil; Solomon, Colin; Hulme, Adam (CRC Press, 2021)
Sport, either through participation or spectatorship, represents a part of everyday life and plays a key role in our health and well being. It is also big business. When this is considered with the fact that most sports exhibit many of the characteristics of complex safety critical systems, it is not surprising that human factors and ergonomics theory and methods are being used to optimize these systems. This relates to enhancing sport performance, injury prevention, product and equipment design, performance assessment, and systems issues. This book will be a source for communicating sports human factors and ergonomics research, showcase key issues, and inspire further applications